Slope of left ventricular filling as an index of valvular and paravalvular regurgitation in native and prosthetic aortic valves. Issue 7 (18th July 2018) - Makki, Nader; Ghao, Xu; Whitson, Bryan; Shreenivas, Satya; Crestanello, Juan; Lilly, Scott
Abstract: Background: Precise quantification of paravalvular aortic regurgitation (PAR) is challenging. Aortic regurgitation index (AR index) has been validated in transcatheter aortic valve replacement (TAVR) cohorts; however, accuracy is limited by heart rate dependency. Diastolic pressure time (DPT) index has been suggested as an alternative and also predicts mortality after TAVR. We chose to evaluate the left ventricular diastolic filling slope (LVDFS) as a surrogate of AR, and suggest it is less heart rate dependent than the AR index and comparable to DPT index. Methods: For initial validation, we compared the LVDFS between three cohorts of patients with native aortic valves referred for hemodynamic assessment: (1) Patients without AR; (2) moderate AR; and (3) severe AR. We then retrospectively identified TAVR patients between January 2012 and 2017, and compared LVDFS to echocardiographic PAR. Results: In both TAVR patients and those patients with native aortic valve disease, the LVDFS showed a stepwise increase with increasing echocardiographic AR severity. When compared to AR or DPT indices, LVDFS better discriminated the degree of AR in native valves and post‐TAVR when AR is primarily paravalvular. Additionally, the slope did not considerably change across a spectrum of heart rates in both native and post‐TAVR populations. Conclusions: The LVDFS is a simple, reproducible metric that can be operationalized in patients undergoing TAVR, as well as those with native valve regurgitation. Additional studies are necessary to determine the relationship between LVDFS and post‐TAVR outcomes.